DEPRESSED HOUSEWIVES AS RESULTS OF WOMAN-OPPRESSION FOUND IN SHORT-STORIES: A COMPARATIVE LITERATURE STUDY - Fransiska Marsela Hambur (Universitas Stikubank (UNISBANK) Semarang, 2019)
Literature represents and portrays variation of society and all human life’s aspects. This includes common happenings. On behalf of this matter, there is an importance to study the literature as a model of real life and society, followed by certain phenomena happened in certain time. For ages, oppression and depression are one of frequents phenomena. Oppressions are often found in women, especially in housewives. This may lead to implication that housewives may undergo psychological problem, such as depression. In literary work, both woman-oppression and depression are often found in many kinds of works, such as movie and short-story. This research focused on two short-stories written by Thomas Hardy “An Imaginative Woman” (1893) and Jhumpa Lahiri “Interpreter of Maladies” (1999). Both were analyzed using feminism and psychoanalysis approach in terms of proving the hypothesis that woman-oppression can become source of depression in housewives’ lives. The findings showed that domestic women, especially those who only work as housewives experienced depression because of their lack of social-connection. In both short-stories, the depressed housewives would lead her life into troublesome habits, such as having delusions, having affair beyond marriage, being ignorant toward her family, being in destructive behaviors, and even wishing her own death. This findings surely became an implication that women-oppression will indeed lead women into self-destructing behaviors.